Profile and characteristics of the visits of international visitors to the Kilim Karst Geoforest Park, Langkawi - Matthew, Nitanan Koshy; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (2013)
Kilim Karst Geoforest Park offers rural tourism attractions to visitors from various countries in the world. The information collected from visitors to the park allows categorization to be done on groups of people who visited the park, and such information can be utilized for marketing purposes. Therefore, the objectives of this paper are to identify the profile and the characteristics of visits by international visitors. Besides, it is also to measure their level of satisfaction on the quality of the facilities and resources and their willingness to pay for the entrance fee of the park. Structured questionnaire and face-to-face data collection method were employed to obtain primary data from 330 international visitors. The raw data is presented in a simpler form using the Statistical Package for the Social Sciences (SPSS) version 21. The findings suggest that majority of the respondents have high level of education, they earn less than RM6,000, they are first time visitors, they are originate from the European continent, and they work in the private sector. Next, 66% of the respondents did not use any tour package either from home or at Langkawi. Willingness to pay (WTP) for an entrance fee is low (less than RM40) although they are satisfied with the resources available at the park. The findings would be useful for the Langkawi Development authority (LADA) in making decisions concerning marketing purposes of the park.